Relatório de Estágio Profissional: À descoberta do caminho para ser Professora" - Leonor Macedo Tavares Tschopp (2019)
This document is part of the realization of my Professional Internship, a curricular unit present in the 2nd Cycle in Physical Education Teaching in Basic and Secondary Education, of the College of Sport of the University of Porto. It emerged as an opportunity to put into practice the knowledge gained during my formative years and to transfer them into the real context, the school.Throughout the same I will report on my evolutionary process as a teacher, namely the learning, the obstacles, the decisions and strategies taken, the solutions and lessons encountered, and all the experiences I had with my 11th grade class, which were essential for my personal and professional development.This report is organized into five chapters. The first, the "Introduction", contextualizes and shows the purpose of this document, as well as some relevant concepts supported in the literature. The second, the "Personal Framing", refers to my life history, the experiences that guided me along this path and justify the choices made, my expectations and confrontation with the reality, as well the role of the internship. The third, the "Framework of Professional Practice ", portrays the professional internship at institutional, legal and functional level, and an analysis and characterization of the school that welcomed me and of all the actors in its community, including my cooperating teacher, my internship group and my resident class. The fourth, the "Realization of Professional Practice", refers to some concecpts essencial to practice, and it's divided into three areas: the area of Organization and Management of Teaching and Learning; the area of School Participation and community relations; and the Professional Development area, which includes my research-action study. The fifth, "Conclusion and Future Perspectives," where I take stock of the completion of this internship year and my ambitions for what follows.